CYBER WARFARE THREATS AND ANALYZING READINESS OF THE INDONESIAN NAVY IN PRIORITIZING VARIABLES - Rakam, Rakam; Imron, Choirul; Purnomo, Joko; Hartoko, Priyadi (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2023)
The advancement of information technology has greatly impacted various aspects of human life, including the Indonesian Navy. This progress has given rise to the concept of Cyber Warfare, which involves conducting warfare through information technology. Cyber warfare refers to actions taken by a country or international organization to attack and undermine another country's computer or information networks, typically through means like viruses or denial of service attacks.In light of these circumstances and challenges, the authors undertook an analysis to assess the readiness of the Indonesian Navy in dealing with the threat of cyber attacks, both domestically and internationally. This research employed cyber warfare threat modelling, which involved weighing and prioritizing key variables such as offensive cyber operations, cyber espionage operations, and cyber support. The objective of this study was to develop a Cyber Warfare threat model to support the responsibilities of the Indonesian Navy. Data processing for this research involved collecting relevant data from activities conducted at Satsiberal Headquarters, which was then analyzed using Fuzzy weighting. Additionally, the Dynamic System modelling method was employed to ascertain the interrelationships between variables and simulate the best alternative scenario. The results of the modellingg and simulation provided valuable insights for addressing the cyber warfare threat effectivelyKeywords: Cyber Warfare Threats, Indonesian Navy, Dynamic System.